2011
DOI: 10.1063/1.3567945
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory measurements and theoretical modeling of seismoelectric interface response and coseismic wave fields

Abstract: A full-waveform seismoelectric numerical model incorporating the directivity pattern of a pressure source is developed. This model provides predictions of coseismic electric fields and the electromagnetic waves that originate from a fluid/porous-medium interface. An experimental setup in which coseismic electric fields and interface responses are measured is constructed. The seismoelectric origin of the signals is confirmed. The numerically predicted polarity reversal of the interfacial signal and seismoelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…This boosted the geophysical research on seismo‐electromagnetic phenomena. Several laboratory experiments [e.g., Jouniaux and Pozzi , ; Zhu and Toksöz , ; Schakel et al , ], numerical modeling experiments [e.g., Haartsen and Pride , ; Haines and Pride , ; Garambois and Dietrich , ; Zyserman et al , ; Grobbe and Slob , ; Kröger et al , ; Grobbe et al , ; N. Grobbe et al, Comparison of eigenvectors for coupled seismo‐electromagnetic layered‐Earth modeling, submitted to Geophysical Journal International , 2015], and field tests [e.g., Butler et al , ; Thompson et al , ; Dean et al , ] have been carried out in attempts to understand this complex physical phenomenon better and to develop applications for the geophysical community.…”
Section: Introductionmentioning
confidence: 99%
“…This boosted the geophysical research on seismo‐electromagnetic phenomena. Several laboratory experiments [e.g., Jouniaux and Pozzi , ; Zhu and Toksöz , ; Schakel et al , ], numerical modeling experiments [e.g., Haartsen and Pride , ; Haines and Pride , ; Garambois and Dietrich , ; Zyserman et al , ; Grobbe and Slob , ; Kröger et al , ; Grobbe et al , ; N. Grobbe et al, Comparison of eigenvectors for coupled seismo‐electromagnetic layered‐Earth modeling, submitted to Geophysical Journal International , 2015], and field tests [e.g., Butler et al , ; Thompson et al , ; Dean et al , ] have been carried out in attempts to understand this complex physical phenomenon better and to develop applications for the geophysical community.…”
Section: Introductionmentioning
confidence: 99%
“…For ultrasonic frequency bandwidths, the numerical instabilities associated with the parts of the eigenvector sets involved in describing the Biot slow wave might become more pronounced, thereby increasing the importance of numerically precise and stable modelling. Typical seismo-electromagnetic laboratory wave propagation experiments (Schakel et al 2011;Smeulders et al 2014;Zhu et al 2000;Zhu & Toksöz 2005) make use of these ultrasonic frequencies due to the small scale of the experiments. Wave-induced fluid flow modelling for laboratory experiments is recently further addressed by Jougnot et al (2013): using numerical simulations of oscillatory compressibility tests coupled to a model for seismo-electromagnetic conversion in the quasi-static approach, they demonstrate that mesoscopic heterogeneities can produce measurable seismo-electromagnetic signals for typical laboratory configurations.…”
Section: Discussionmentioning
confidence: 99%
“…From the Pf-wave speed (see Table 1) and the thickness of the sample (2 cm), we conclude that a second interface response pulse generated at z = 2 cm will overlap in time with the first pulse that arrives at around 94 μs, i.e., it arrives approximately 6 μs later, and therefore, will also generate electric signals up to 6 μs later. Schakel et al (2011a) showed that by expanding Eq. 9 with appropriate seismoelectric and mechanical reflection and transmission coefficients and wave propagation terms, additional interface response fields that are generated by seismic waves that scatter within the sample can be described.…”
Section: Pressure and Electric Measurementsmentioning
confidence: 99%
“…They also confirm the electrokinetic nature of the signals. Schakel et al (2011a) develop a full-waveform seismoelectric model based on the seismoelectric theory as derived by Pride (1994) and Pride and Haartsen (1996) and show that the model properly predicts laboratory measurements of coseismic and interface response fields in terms of travel time, waveform, polarity, amplitude, and spatial amplitude decay. In a similar way, Schakel et al (2011b) compare full-waveform fluid/porous-medium interface response predictions as a function of salinity and distance to the interface.…”
Section: Introductionmentioning
confidence: 99%